2004
DOI: 10.1007/bf02985098
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon agents for tumor imaging:201TI,99mTc-MIBI, and99mTc-tetrofosmin

Abstract: This review aims at fostering comprehension and knowledge not only for expert physicians who can skillfully handle various techniques for tumor imaging but also for young practitioners in the field of nuclear medicine. As image processing software and hardware become smaller, faster and better, SPECT will adapt and incorporate these advances. A principal advantage of SPECT over PET is the more widespread availability of the equipment and lower cost for the introduction of the system in community-based faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 67 publications
0
35
0
5
Order By: Relevance
“…However, small dimension of HP, oxyphil cell content, and various degree of apoptosis or necrosis may reduce MIBI uptake causing false-negative results (18,19). On the other hand, MIBI retention is not parathyroid specific and is also observed in hypermetabolic thyroid nodules (TNs) such as oncocytic tumors (20) and autonomous thyroid adenomas (TA) (20,21). Neck US is the least invasive and cheapest method (11,22) to accurately localize HP, but its efficacy is related to the operator experience and may be reduced in the presence of concomitant nodular goiter (NG) (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…However, small dimension of HP, oxyphil cell content, and various degree of apoptosis or necrosis may reduce MIBI uptake causing false-negative results (18,19). On the other hand, MIBI retention is not parathyroid specific and is also observed in hypermetabolic thyroid nodules (TNs) such as oncocytic tumors (20) and autonomous thyroid adenomas (TA) (20,21). Neck US is the least invasive and cheapest method (11,22) to accurately localize HP, but its efficacy is related to the operator experience and may be reduced in the presence of concomitant nodular goiter (NG) (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, increased retention of MIBI is currently employed to detect hyperfunctioning parathyroid tissue (21,22) and may be observed in benign or malignant thyroid tumours, especially of oncocytic nature (23). Increased MIBI retention has also been described in hyperfunctioning thyroid tissue (toxic adenoma or toxic diffuse goitre) (24,25) and this phenomenon is believed to be the consequence of increased mitochondria number in hypermetabolic cells (26,27). On the other hand, MIBI accumulation is reduced or absent in apoptotic or necrotic processes involving mitochondrial membrane potential collapse (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Using the amino acid analog 3-123 I-iodo-L-methyltyrosine in patients with resected gliomas, Weber et al reported that the intensity of tracer uptake significantly correlated with survival (8). 99m Tc-labeled compounds have also been studied in brain tumors and were proven advantageous over 201 Tl (15). 99m Tc-sestamibi has been extensively used and proved useful for metabolic characterization (16).…”
Section: Discussionmentioning
confidence: 99%